Dicer deficiency affects microglial function during demyelination and impairs remyelination - Ajai Tripathi; Nagendra Kumar Rai; Aaron Perles; Haley Courtney; Claire Jones; Adya Sapra; Jason Plemel; Ranjan Dutta (Neurobiology of Disease)
Microglia are essential regulators of central nervous system (CNS) homeostasis, playing key roles in demyelination and remyelination. Dysregulated microglial activity contributes to pathological inflammation and impaired repair processes in demyelinating diseases. Here, we investigate the role of Dicer1, a critical enzyme in microRNA biogenesis, in affecting microglial function, demyelination, and remyelination. Loss of Dicer1 in microglia resulted in amplified inflammatory responses, defective myelin debris clearance, and disruption of metabolic homeostasis, leading to exacerbated demyelination and delayed remyelination. Transcriptomic analysis revealed significant upregulation of inflammatory pathways, including interferon signaling and JAK/STAT activation, alongside a loss of homeostatic microglial gene expression. Protein-level validation confirmed sustained secretion of pro-inflammatory cytokines such as IFN-γ, IL-16, and CXCL12, creating a chronic inflammatory environment that impaired remyelination. Furthermore, Dicer1-deficient microglia failed to support oligodendrocyte progenitor cells (OPCs) differentiation/maturation, with increased apoptosis of mature oligodendrocytes (OLs), contributing to remyelination failure. These findings identify Dicer1 as a critical regulator of microglial homeostasis and inflammation resolution, highlighting its potential as a therapeutic target to mitigate inflammation and promote repair in demyelinating diseases.